The Past Rebuilt (Bulletin KNOB, 1995)
In this article the authors argue that in attempts to reconstruct lost historical church buildings, it is advisable not just to make drawings, hut also to produce reconstruction scale-models representing both the interiors and exteriors as accurately as possible.As an example the reconstruction model of the lost medieval Maria Church in Utrecht is referred to, one of a series of 15 reconstruction models so far, all to a scale of 1:200, of lost or mutilated, prominent churches of Western Christianity from the Roman period to the late Middle Ages.A corrected reconstruction model of the Romanesque choir is described on the basis of a publication on the subject of the excavation after the fire of the K & W building (Art & Science Building) in 1988. The preliminary study and the actual making of the reconstruction model have resulted in conclusions deviating from the ones drawn in any publications on reconstruction drawings, interpretations of Pieter Saenredam's representations and a description of a reconstruction.